Electro-optic imaging enables efficient wide-field fluorescence lifetime microscopy - Adam J. Bowman (Nature Portfolio, 2019)
Nanosecond imaging techniques, such as fluorescence lifetime imaging microscopy (FLIM), are limited by low efficiency of current detectors. Here, the authors implement an electro-optic approach using Pockels cells for wide-field image gating and demonstrate high throughput FLIM on standard camera sensors.